Risk factors and postoperative comfort nursing in adolescents with flatfoot complicated by idiopathic scoliosis - Jiang, Suzhen; Lin, Meiya; Wang, Xiaofang (Frontiers in Pediatrics, 2025)
ObjectiveAdolescent flatfoot complicated by idiopathic scoliosis (AIS) are common musculoskeletal disorders, yet their shared risk factors and postoperative management remain underexplored. Current study aims to investigate podiatric risk factors for AIS in flatfoot patients and evaluates the efficacy of comfort nursing on postoperative nausea and vomiting following corrective surgery.MethodA two-phase study was conducted. First, 193 flatfoot patients were categorized into AIS (n = 144) and non-AIS (n = 49) groups to analyze risk factors via logistic regression. Second, the AIS patients undergoing PCS were randomized into a control group (routine care, n = 72) and a comfort nursing (CN) group (n = 72). The incidence, frequency, and severity of PONV, vital signs, medication use, and recovery outcomes were compared.ResultsAge, hallux valgus angle asymmetry (ΔHVA), and Meary's angle asymmetry (ΔMA) were identified as independent risk factors for AIS in flatfoot patients. The CN group exhibited a significantly lower incidence of PONV [13/72 (18.06%) vs. 35/72 (48.61%)] and lower frequency of episodes compared to the control group (P < 0.001). The CN intervention also resulted in significantly reduced pain VAS scores, improved vital signs (temperature and urine output), less severe PONV-related symptoms, decreased antiemetic use, and enhanced overall recovery and patient satisfaction (all P < 0.05).ConclusionAsymmetric foot morphology (ΔHVA and ΔMA) is a significant risk factor for AIS in adolescents with flatfoot. Implementing a multidimensional comfort nursing protocol effectively mitigates PONV, alleviates discomfort, and promotes postoperative recovery after PCS, suggesting that this approach could represent a valuable strategy for improving clinical outcomes in similar settings.